2022
DOI: 10.1021/acs.cgd.2c00178
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Columnar Organization of Partially Fluorinated Dehydrobenz[18]annulenes

Abstract: Two diamond-shaped and partially fluorinated dehydrobenz[18]annulene macrocycles have been prepared through a one-pot synthesis relying on four-fold Sonogashira coupling. Single-crystal structures of these macrocycles show continuous columnar stacks held together by the fluoroarene−alkyne, arene−alkyne, fluoroarene−fluoroarene, and alkyne−alkyne [π•••π] interactions instead of the expected fluoroarene−arene [π•••π] interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Although analysis by Moore and co-workers in 1996 of structures in the CSD concluded that “π–π stacking between triple bonds and aromatic rings is not a particularly significant noncovalent interaction”, 37 recent work from Karki et al suggests that intermolecular π–π interactions between alkynes and fluoroarenes are significant in influencing solid-state packing. 38 We were, therefore, interested to see whether the incorporation of the terminal alkyne moieties in ligands 1–3 would lead to intramolecular interactions involving the CCH unit and arene domains in [Cu(N^N)(P^P)][PF 6 ] complexes (N^N = 1–3 , P^P = POP or xantphos).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although analysis by Moore and co-workers in 1996 of structures in the CSD concluded that “π–π stacking between triple bonds and aromatic rings is not a particularly significant noncovalent interaction”, 37 recent work from Karki et al suggests that intermolecular π–π interactions between alkynes and fluoroarenes are significant in influencing solid-state packing. 38 We were, therefore, interested to see whether the incorporation of the terminal alkyne moieties in ligands 1–3 would lead to intramolecular interactions involving the CCH unit and arene domains in [Cu(N^N)(P^P)][PF 6 ] complexes (N^N = 1–3 , P^P = POP or xantphos).…”
Section: Resultsmentioning
confidence: 99%
“…To the best of our knowledge, there has been little detailed discussion of such alkyne⋯arene π-interactions (intra-or intermolecular) in the literature. 37,38 We therefore decided to search the CSD using Conquest (version 2022.3.0 including November 2022 updates) 27 with a focus on intramolecular CC⋯arene contacts; 'arene' was defined as an aromatic C 6 ring with no constraints on substituents, and an initial search had no restriction on the groups attached to the alkyne unit. The CC unit was defined with a terminal hydrogen atom in a second search.…”
Section: Preparation and Characterization Of The Copper(i) Complexesmentioning
confidence: 99%
“…Dehydrobenzannulenes (DBAs) attract intensive attention because they often show new functionality for -expanded compounds, such as a novelinteraction mode in fluoroarylene-DBA (Karki et al, 2022), guest-dependent structuretransformative DBA inclusion crystals (Shigemitsu et al, 2012), and a synthetic intermediate of [6.8] 3 cyclacene (Esser et al, 2008). In the syntheses of DBAs, ethenylene and ethynylene arrays are often used to connect aromatic rings to one another.…”
Section: Chemical Contextmentioning
confidence: 99%